Dermoscopy of branchial fistula - Subrata Malakar; Priya Diwaker; Pratibha Pradhan (Wolters Kluwer Medknow Publications, 2018)
Branchial fistula is a congenital anomaly resulting from failure of closure of one of the four branchial clefts. It is usually a clinical diagnosis, but dermoscopy helps in highlighting its features, thereby avoiding the need of imaging studies and other invasive diagnostic procedures. Here, we report a case of 3-year-old female patient who presented with asymptomatic tiny papule on the neck since early childhood. Dermoscopy was done to describe the features of branchial fistula and cleft.